Development of anorthite based white porcelain glaze without ZrSiO4 content. Issue 2 (1st February 2017) - Gajek, Marcin; Partyka, Janusz; Rapacz-Kmita, Alicja; Gasek, Katarzyna
Abstract: The aim of this study was to develop new compositions of white glazes without the addition of ZrSiO4 designed for sanitary products obtained in a 12-h firing cycles at a maximum temperature of 1230 °C. Alternative glazes with a good opacity and a high degree of whiteness were obtained, composed primarily of raw materials available on the domestic market in Poland. The opaque effect was achieved due to crystallisation of anorthite, which was identified as a major crystalline phase in the system. The glazes were characterised by a high whiteness value L*, greater than 90 in the CIELAB colour space, and a gloss, measured with a 60° light incident angle on the glaze surface, above 50%. The microstructure and structure of the glazes were measured with the use of a Scanning Electron Microscope (SEM) and X-ray Diffraction (XRD). The colour and gloss of glazes were measured with the use of a spectrophotometer and a gloss metre at a 60° angle of incidence. The topography of glazes surfaces, as well as the roughness level (Ra), were measured with the use of a confocal microscope.